1997
DOI: 10.1111/j.1440-0960.1997.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive vesiculobullous eruption following limited ruby laser treatment for incontinentia pigmenti: A case report

Abstract: A 3-year-old girl with incontinentia pigmenti was referred for treatment of pigmented whorled macules on the trunk and limbs. Initially ruby laser therapy was only given to the legs. Wound healing was delayed. Two months later the patient developed extensive vesicles and erosions restricted to pigmented macules in both treated and untreated areas. Conservative treatment, including 2 weeks hospitalization, improved acute inflammation, but the remaining pigmentation was darker than originally seen. The apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…A trigger factor is frequently reported. 18 This phenomenon could be explained by the persistence of residual NEMO-deficient cells giving rise to hyperproliferation, inflammation, and apoptosis until there is a complete elimination of the mutated cells from the skin. 19 The role of proinflammatory cytokines such as tumor necrosis factor (TNF)-a has been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A trigger factor is frequently reported. 18 This phenomenon could be explained by the persistence of residual NEMO-deficient cells giving rise to hyperproliferation, inflammation, and apoptosis until there is a complete elimination of the mutated cells from the skin. 19 The role of proinflammatory cytokines such as tumor necrosis factor (TNF)-a has been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…No triggering factor was noted. Nagase et al 9 reported the recurrence of a linear vesiculobullous rash following a laser treatment for hyperpigmented areas. As in our cases, no resurgence of extracutaneous involvement, ophthalmologic or neurologic, was experienced in any of these cutaneous exacerbations.…”
Section: Commentmentioning
confidence: 99%
“…Until now, only a few cases of such late recurrences have been reported, and these were not well explained. [5][6][7][8][9] This phenomenon seems to be uncommon but may be misdiagnosed. Our 5 cases were gathered through analysis of a series of 40 children observed for IP in our dermatologic unit.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The frequency of such late recurrences, sometimes several years after the neonatal period, remains unknown. [16][17][18][19] Thus, a diagnosis of IP could be considered in the case of a child presenting with recurrent inflammatory lesions of unknown origin along the Blaschko lines. The frequency of stage 2 verrucous and keratotic lesions in our series was consistent with published data (80% vs 70%, Figure 1B), as well as the lesions' time of appearance (within the first 2 months of life) and duration (they cleared within 6 months).…”
Section: Commentmentioning
confidence: 99%